Design of TiO2-Based Hybrid Systems with Multifunctional Properties - Simona Ortelli; Maurizio Vespignani; Ilaria Zanoni; Magda Blosi; Claudia Vineis; Andreana Piancastelli; Giovanni Baldi; Valentina Dami; Stefania Albonetti; Anna Luisa Costa (Molecules)
In recent years, multifunctional inorganic−organic hybrid materials have been widely investigated in order to determine their potential synergetic, antagonist, or independent effects in terms of reactivity. The aim of this study was to design and characterize a new hybrid material by coupling well-known photocatalytic TiO2 nanoparticles with sodium surfactin (SS), a biosurfactant showing high binding affinity for metal cations as well as the ability to interact with and disrupt microorganisms’ cell membranes. We used both chemical and colloidal synthesis methodologies and investigated how different TiO2:SS weight ratios affected colloidal, physicochemical, and functional properties. We discovered a clear breaking point between TiO2 and SS single-component trends and identified different ranges of applicability by considering different functional properties such as photocatalytic, heavy metal sorption capacity, and antibacterial properties. At low SS contents, the photocatalytic properties of TiO2 are preserved (conversion of organic dye = 99% after 40 min), and the hybrid system can be used in advanced oxidation processes, taking advantage of the additional antimicrobial SS properties. At high SS contents, the TiO2 photoactivity is inhibited, and the hybrid can be usefully exploited as a UV blocker in cosmetics, avoiding undesired oxidative effects (UV adsorption in the range between 300–400 nm). Around the breaking point (TiO2:SS 1:1), the hybrid material preserves the high surface area of TiO2 (specific surface area around 180 m2/g) and demonstrates NOx depletion of up to 100% in 80 min, together with improved adhesion of hybrid antibacterial coating. The last design demonstrated the best results for the concurrent removal of inorganic, organic, and biological pollutants in water/soil remediation applications.